Analysis Of Defaults In Employment Based Contract Agreements The Value Of Justice - Nabila Gelasia Herta Ananda; Darwis Anatami; Fadlan Fadlan; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Through Law Number 11 of 2020 concerning Job Creation and its derivative PP Number 35 Thuan 2021 concerning PKWT, Outsourcing, Working Time and Rest Time and Termination of Employment Relations is the crystallization of various laws regarding Employment. which, philosophically, does not provide guarantees and protection for workers' rights. Methodologically, this research is an empirical juridical research using a combined approach method which is carried out by analyzing the research explanation in an inductive way leading to a deductive method so as to help the author explain the relationship between research variables and research objects. The results of this research found that there are many deficiencies in Law Number 13 of 2003 concerning Employment, such as the absence of legal protection or workers who are in non-standard work relationships, gender discrimination, wages, lack of social security, leave rights and other rights, partial revision What the Job Creation Law does to the Employment Law Number 13 of 2003 actually creates new problems that have a negative impact on worker protection, the rules governing employment now, so that if you look closely at the revised and deleted articles, it appears that The spirit of the law does not at all touch on efforts to increase worker competency, even though in reality, in Pancasila industrial relations, worker protection is a form of government responsibility. So it is hoped that a legal political policy between the DPR and the government will make changes to Article 66 paragraph (2) of Law Number 3 of 2023 concerning the Determination of Perpu Number 2 of 2022 into the Job Creation Law and PP Number 35 of 2021 concerning Specific Time Work Agreements , Outsourcing, Working Time and Rest Time, and Termination of Employment Relations, so that it can be seen more clearly how the protection of workers/laborers, wages, welfare, and protection of the special rights of outsourced workers, especially outsourced workers, must ensure greater legal protection so that the working atmosphere can become better and more conducive and neither party feels disadvantaged